2022
DOI: 10.3390/s22020647
|View full text |Cite
|
Sign up to set email alerts
|

An Authentication and Secure Communication Scheme for In-Vehicle Networks Based on SOME/IP

Abstract: The rapid development of intelligent networked vehicles (ICVs) has brought many positive effects. Unfortunately, connecting to the outside exposes ICVs to security threats. Using secure protocols is an important approach to protect ICVs from hacker attacks and has become a hot research area for vehicle security. However, most of the previous studies were carried out on V2X networks, while those on in-vehicle networks (IVNs) did not involve Ethernet. To this end, oriented to the new IVNs based on Ethernet, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In order to prevent these attacks, a symmetric cryptographic encryption scenario scheme is proposed, and its feasibility is verified. Reference [32] designs an authentication scheme in the vehicle domain, and the security analysis of the Proverif analysis tool shows that the designed scheme can effectively resist malicious attacks. The model detection method proposed by us can detect the security anomalies of the protocol, and through the model, it can more intuitively show what security vulnerabilities exist in the protocol under what kind of attack type.…”
Section: Improvement Scheme Performance Analysis and Methods Comparisonmentioning
confidence: 99%
“…In order to prevent these attacks, a symmetric cryptographic encryption scenario scheme is proposed, and its feasibility is verified. Reference [32] designs an authentication scheme in the vehicle domain, and the security analysis of the Proverif analysis tool shows that the designed scheme can effectively resist malicious attacks. The model detection method proposed by us can detect the security anomalies of the protocol, and through the model, it can more intuitively show what security vulnerabilities exist in the protocol under what kind of attack type.…”
Section: Improvement Scheme Performance Analysis and Methods Comparisonmentioning
confidence: 99%
“…To ensure the secure usage of SOME/IP, there are various papers [ 13 , 14 , 15 , 16 , 17 ] available. Among them, I have compared two early papers with my own research.…”
Section: Related Workmentioning
confidence: 99%
“…An efficient secure authentication scheme was proposed in [26], utilizing scalable service-oriented middleware over IP (SOME/IP) practice and a protected data exchange method altering the payload field of the original SOME/IP message. The security evaluation showed that the proposed authentication system can offer joint authentication and guarantee the secrecy of the released interim session key; and can avoid the common malicious incidents jointly.…”
Section: Cryptography: Authentication and Encryption Algorithmsmentioning
confidence: 99%